Performa Pertumbuhan Nannochloropsis sp. pada Berbagai Media Limbah Akuakultur - Sara Serina Sitepu; Rosmaiti Rosmaiti; Teuku Fadlon Haser; Suri Purnama Febri (Fakultas Pertanian Universitas Samudra, 2025)
Nannochloropsis sp. is a microalga widely used as natural feed, particularly for rotifers, Artemia, and the larvae of fish and shrimp. During cultivation, this microalga requires essential nutrients such as nitrate and phosphate to support photosynthesis and growth. Aquaculture pond wastewater often contains organic matter that can cause environmental pollution but may also serve as a potential nutrient source for microalgal culture. This study aimed to evaluate the growth performance of Nannochloropsis sp. in different aquaculture wastewater media. The experiment was conducted from September to October 2021 using a Completely Randomized Design (CRD) with four treatments: P0 (control/seawater), P1 (vannamei shrimp pond wastewater), P2 (milkfish pond wastewater), and P3 (grouper pond wastewater), each with three replications. The results showed that P1 produced the highest growth performance, with cell density reaching 2.15 × 10⁶ cells/ml. These findings indicate that shrimp pond wastewater can be utilized as an alternative medium for microalgal cultivation while simultaneously supporting sustainable aquaculture waste management.